(untitled) (International Journal of Irrigation and Water Management, 2017)
With the goal of reducing cost and energy consumption of drip irrigation systems, the relationship between pressure and cost of drip irrigation systems, as well as the feasibility of reducing the operating pressure, were analyzed. The irrigation quality and reliability of micro-pressure drip irrigation systems were also studied. A theory of micro pressure drip irrigation technology is proposed, and the components of this type of irrigation system are presented. The results indicate that micro-pressure drip irrigation technology is feasible and that it can significantly decrease initial drip irrigation system cost and recurring operating expenses. Micro-pressure drip irrigation can also overcome some of the clogging problems of conventional drip irrigation systems. It is suggested that micro-pressure drip irrigation will be a topic of importance in the future of agriculture and environmental biotechnology.